Fuel-cell energy generation system based on the series-capacitor boost converter. (26th July 2021) - Rosas-Caro, Julio C.; Valdez-Resendiz, Jesus E.; Mayo-Maldonado, Jonathan C.; Sanchez, Victor M.; Lopez-Nuñez, Adolfo R.; Barbosa, Romeli; Valdivia, Leonardo J.
Abstract: This work introduces the development of a power-electronics customizable energy system for their application on renewable energy generation based on proton-exchange membrane fuel cells. The customizable energy system aims to regulate the output voltage from a fuel cell, which has a relatively low amplitude and wide range of variation, to a fixed voltage to feed a grid-tie inverter. The customizable energy system proposed is based on a dc-dc converter for which different configurations (topologies) are available, such as the traditional single-phase boost or the (interleaved) multi-phase boost. The dc-dc converter of the energy system is based on the series-capacitor boost converter, a recently proposed converter that has a similar configuration to the interleaved boost converter. This article shows that the series-capacitor boost topology offers benefits in the proposed application. An experimental prototype was developed and tested in order to demonstrate the advantages of the system proposed. Highlights: The development of power-electronics customizable energy system for PEMFC is presented. The system is based on the series-capacitor boost converter. Experimental results are provided to demonstrate the advantages of the system.